PENENTUAN JUMLAH PERSEDIAAN SUKU CADANG RANTAI GARU MESIN PENGGILING TEBU BERDASARKAN TINGKAT KEKRITISAN KOMPONEN MODEL ABC MENGGUNAKAN SPARE PART REQUIREMENT NOMOGRAPH - Sodikin, Imam (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
Madukismo is one of the companies operating in the area of agroindustry with sugar as the main product. In order to exist, the company needs to increase the work effectiveness and efficiency in using the production machines through the planning of maintenance scheduling in order that the machines or units that are going to be used can be operated well, and work properly.The aim of this research is to analyze level requirement of amount of spare-part optimal with Sparepart requirement nomograph approach. This effort is able to increase high production quality, availability and reliability by maximizing equipments age, and also exploiting of effective maintenance. Based on the research result shows that the maintenance of chain eye component, it should be differentiated, basically, on the maintenance time. Determination of feed amounts at